Classroom Display Management As a Determinant Factor of Primary School Students' Learning Achievement - Siti Dewi Maharani (Al Ibtida: Jurnal Pendidikan Guru MI, 2023)
AbstractClassroom management has a significant role in supporting effective teaching and learning activities; however, many teachers have not implemented aspects of classroom management and often ignore these aspects. This study aims to determine the effectiveness of classroom management on student’s learning achievement. The research method was conducted using a quantitative approach to 30 students at Elementary School in Rambang Niru, South Sumatera, Indonesia through determinant coefficient data analysis techniques to determine the effectiveness. The results show that seating arrangements contributed by 0.64%, volume and intonation by 1.46%, speech by 0.63%, feedback by 0.85%, material adjustment by 0.63%, rulemaking by 0.19%, respect student opinions by 0.62%, neat and polite appearance by 0.023%, time adjustment by 0.05% and syllabus delivery by 1.92%. Class management data of totaling 30 students, shows that the highest percentage is in the range of 86-95 scores of 50% with a high level category. This shows that class management has been carried out very well. However, classroom management only contributes 7.39% to student’s learning achievement. 92.61% of student’s learning achievement is influenced by other factors, both internal and external factors. Internal factors significantly influence student achievement, although it is undeniable that external factors play a role in determining student’s learning achievement.Keywords: classroom management, determinant factor, learning achievement.AbstrakManajemen kelas memiliki peran yang signifikan dalam mendukung kegiatan belajar mengajar yang efektif. Namun, banyak guru yang belum menerapkan aspek pengelolaan kelas dan sering mengabaikan aspek tersebut. Penelitian ini bertujuan untuk menentukan efektifitas manajemen kelas terhadap prestasi belajar siswa. Metode penelitian dilakukan dengan pendekatan kuantitatif kepada 30 siswa Sekolah Dasar di Rambang Niru, Sumatera Selatan, Indonesia melalui teknik analisis data koefisien determinan untuk mengetahui keefektifannya. Hasil penelitian menunjukkan bahwa pengaturan tempat duduk berkontribusi sebesar 0,64%, volume dan intonasi sebesar 1,46. %, ucapan sebesar 0,63%, umpan balik sebesar 0,85%, penyesuaian materi sebesar 0,63%, pembuatan peraturan sebesar 0,19%, menghargai pendapat siswa sebesar 0,62%, penampilan rapi dan sopan sebesar 0,023%, penyesuaian waktu sebesar 0,05% dan penyampaian silabus sebesar 1,92%. Data pengelolaan kelas yang berjumlah 30 siswa menunjukkan persentase tertinggi berada pada kisaran skor 86-95 sebesar 50% dengan kategori level tinggi. Hal ini menunjukkan pengelolaan kelas sudah dilakukan dengan sangat baik. Namun demikian, pengelolaan kelas hanya memberikan kontribusi sebesar 7,39% terhadap prestasi belajar siswa. 92,61% prestasi belajar siswa dipengaruhi oleh faktor lain, baik faktor internal maupun eksternal. Faktor internal berpengaruh secara signifikan terhadap prestasi belajar siswa, meskipun tidak dipungkiri bahwa faktor eksternal turut berperan dalam menentukan prestasi belajar siswa.Kata kunci: pengelolaan kelas, faktor penentu, prestasi belajar.